Marketing of goat at different age and weight by different categories of farmers in selected areas of Bangladesh (Bangladesh Journal of Animal Science, 2012)
The factors influencing marketing of goats at different age and weight by different categories of farmers were investigated. The data were collected from village market (Hat) in selected places of Sirajgonj, Rajshahi, Kushtia, Mymensingh and Tangail districts. Goat owners belonged to one of the 4 categories of farmers at the Hat were interviewed through pre-tested questionnaire and the weight, body size and age of goats were determined. Landless and marginal farmers sold 58.81% of their goats at 6 months, 42.94% of small farmers at 10.5 months and 50% of medium farmers at 15.5 months of age. The average market weight and age of goats belonged to above categories of farmers were 8.39, 12.89, 17.10 and 17.20 kg and 6, 10.5, 15.5 and more than 18 months of age, respectively. The potential market weight of goats was found 17.10 kg at the age of 15.5 months. About 84% of farmers of all categories sold their goats for cash income, 15% for rearing problems and only 1% for disease prevalence.http://dx.doi.org/10.3329/bjas.v41i1.11979